Tinjauan Kriminologis terhadap Residivis Narkoba - Julkifli Sinaga (Syntax Idea, 2021)
Narcotics are very addictive for consumers, and they can be severely addictive. In fact, nothing ever exists in his good name and a match. In jayapura police jurisdiction, residiat reskrim becomes an internal issue. Criminals who commit suicide after birth in prison are not versatile, which they deter, but they become increasingly intelligent and courageous in their fight against them. Once time passes and where criminal officials for opioid offenders are illegitimate, this is the problem. The purpose of this research used to be for empirical legal analysis where the data of the story and literature of the study. Data analysis of deductive analysis of logic in this study. Where the data process is good, starting with general analysis and drawing is equal to the discussion of a path. In jayapura city police jurisdiction, ex-three reasons for drug recidivist criminology: 1) economic factors, 2) environmental factors, and 3) legal factors.